Comparison of the Effects of Telephone Suicide Prevention Help by Volunteers and Professional Paid Staff: Results from Studies in the USA and Quebec, Canada. Issue 5 (6th March 2016) - Mishara, Brian L.; Daigle, Marc; Bardon, Cécile; Chagnon, François; Balan, Bogdan; Raymond, Sylvaine; Campbell, Julie
Abstract : Research since the 1960s has consistently found that lay volunteers are better at helping suicidal callers than professionals. Yet, professional degrees are increasingly becoming requirements for helpline workers. In our first study, we conducted post hoc comparisons of U.S. helplines with all professional paid staff, all lay volunteers, and a mix of both, using silent monitoring and standardized assessments of 1, 431 calls. The volunteer centers more often conducted risk assessments, had more empathy, were more respectful of callers, and had significantly better call outcome ratings. A second study of five Quebec suicide prevention centers used silent monitoring to compare telephone help in 1, 206 calls answered by 90 volunteers and 39 paid staff. Results indicate no significant differences between the volunteers and paid employees on outcome variables. However, volunteers and paid staff with over 140 hours of call experience had significantly better outcomes. Unlike the United States, Quebec paid employees were not required to have advanced professional degrees. We conclude from these results and previous research that there is no justification for requiring that suicide prevention helpline workers be mental health professionals. In fact, the evidence to date indicates that professionals may be less effective in providing telephone help to suicidal individuals when compared to trained lay volunteers.